Active control of combustion oscillation with active disturbance rejection control (ADRC) method. (8th December 2022) - Zhu, Hongzhi; Weng, Fanglong; Makeximu,; Li, Donghai; Zhu, Min
Abstract: This research aims to develop a novel method for the active control of combustion oscillation based on active disturbance rejection control (ADRC). The effectiveness of parameter tuning and the controller in suppressing combustion oscillation was studied by simulation and experiments. The control performance was verified using a Rijke tube and turbulent premixed swirling flame within a model combustor. For the former, the results show that the first-order ADRC can rapidly mitigate the limit cycle oscillation and maintain the effectiveness of the control when the oscillation frequency changes. For the latter, a system identification method based on an acoustic network was adopted. Combining the identification results with a thermoacoustic network, the formation process of the limit cycle oscillation and the effectiveness of the first-order ADRC were simulated by SIMULINK. The experimental results show that the first-order ADRC performs better than the proportional–integral–derivative (PID) controller. At the same time, the first-order ADRC and second-order ADRC achieve good outcomes when the equivalence ratio changes. However, the second-order ADRC exhibits a better pressure-suppression effect and smaller controller output voltage. Highlights: Limit cycle oscillations are predicted from acoustic network model and experiments. Nonlinear effects of actuator and of flame are modeled by describing functions. Control method is made model-independent by introducing an extended state observer. Active disturbance rejection control presents good robustness when condition shifts.